Strategic Deployment of Emotional-Spiritual Intelligence to Enhance Student Engagement in the Digital Era - Marliana, Thika; Ariestanti, Yenni; Jamiatun, Jamiatun; Indriayani, Iis; Osman, Suhaila Binti; Widayati, Titik; Kurniawati, Indah (Darussalam: Journal of Psychology and Educational, 2025)
In the continuously evolving digital era, the challenge of enhancing student engagement in the teaching and learning process is becoming increasingly complex. This research aims to explore and analyze the strategic application of emotional and spiritual intelligence as tools to enhance student engagement. Emotional intelligence, which includes the ability to recognize, understand, and manage emotions, plays a crucial role in building positive relationships between students and educators. On the other hand, spiritual intelligence allows students to find meaning and purpose in learning, which can enhance their intrinsic motivation. This study uses a qualitative approach by collecting data through surveys, in-depth interviews, and case study analyses in various educational institutions. The research results indicate that the integration of emotional and spiritual intelligence in teaching methods can create a more inclusive, supportive, and responsive learning environment. Students who are emotionally and spiritually engaged show increased academic involvement, better learning outcomes, and higher psychological well-being. Thus, this research recommends that educators adopt strategies that integrate both types of intelligence into their curriculum and teaching practices. These findings are expected to provide insights and guidance for educators to create more meaningful and effective learning experiences in the digital era, as well as to prepare students for future challenges.